2018
DOI: 10.3390/nu10050637
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphatidylserine Source of Docosahexanoic Acid Improves Neurodevelopment and Survival of Preterm Pigs

Abstract: The amount, composition, and sources of nutrition support provided to preterm infants is critical for normal growth and development, and particularly for structural and functional neurodevelopment. Although omega-3 long chain polyunsaturated fatty acids (LC-PUFA), and particularly docosahexanoic acid (DHA), are considered of particular importance, results from clinical trials with preterm infants have been inconclusive because of ethical limitations and confounding variables. A translational large animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
2
24
1
Order By: Relevance
“…Most report no difference in brain DHA accretion or subtle differences between the groups. More recently, other studies have focused on DHA‐PtdSer against a placebo only, DHA esterified to PtdCho or a DHA‐rich phospholipid blend with conflicting results. Others have suggested that DHA‐PtdSer could be efficient in the prevention of cognitive decline or in the treatment of ADHD, but both studies were conducted with a placebo that did not contain DHA as the only comparator.…”
Section: Discussionmentioning
confidence: 99%
“…Most report no difference in brain DHA accretion or subtle differences between the groups. More recently, other studies have focused on DHA‐PtdSer against a placebo only, DHA esterified to PtdCho or a DHA‐rich phospholipid blend with conflicting results. Others have suggested that DHA‐PtdSer could be efficient in the prevention of cognitive decline or in the treatment of ADHD, but both studies were conducted with a placebo that did not contain DHA as the only comparator.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm pigs were obtained via caesarean section at gestation day 105 (which corresponds to 91% of 115-day term). This stage of development is relevant to preterm infants born at week 32 [16]. A feeding tube and an umbilical artery catheter (Umbili-Cath, Utah Medical Products, Midvale, UT, USA) were placed in each preterm pig.…”
Section: Experimental Design Preterm Pig Model and Tissue Collectionmentioning
confidence: 99%
“…The amount of DHA that accumulates in the brain is higher when DHA is conjugated to PS, compared to triacylglycerol, likely because of the superior ability of PS-DHA to cross the blood-brain barrier [24,25]. Recently, using preterm pigs as a translational model for preterm infants, we showed that the use of a formula supplemented with PS-DHA results in cerebella that are heavier than those of control preterm pigs and not significantly smaller than those of pigs born at term [16]. This suggests that PS-DHA helps to promote cerebellar growth after preterm birth, but whether it enhances the development of specific cerebellar populations or key cerebellar developmental processes remains unknown.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…preclinical evidence suggesting that n-3 LCPUFAs, such as DHA are neuroprotective (26)(27)(28). Inflammation appears to play an important causal role in preterm birth, with ongoing inflammatory responses evident in the post-natal period (29).…”
Section: Introductionmentioning
confidence: 99%